Acute exercise and physiological insulin induce distinct phosphorylation signatures on TBC1D1 and TBC1D4 proteins in human skeletal muscle. (23rd December 2013) - Treebak, Jonas T.; Pehmøller, Christian; Kristensen, Jonas M.; Kjøbsted, Rasmus; Birk, Jesper B.; Schjerling, Peter; Richter, Erik A.; Goodyear, Laurie J.; Wojtaszewski, Jørgen F. P.
Key points Phosphorylation signature patterns on TBC1D1 and TBC1D4 proteins in the insulin–glucose pathway were investigated in human skeletal muscle in response to physiological insulin and exercise. In response to postprandial increase in insulin, Akt phosphorylation of T308 and S473 correlated significantly with sites on TBC1D1 (T596) and TBC1D4 (S318, S341, S704). Exercise induced phosphorylation of TBC1D1 (S237, T596) that correlated significantly with activity of the α2/β2/γ3 AMPK trimer, whereas TBC1D4 phosphorylation (S341, S704) with exercise correlated with activity of the α2/β2/γ1 AMPK trimer. TBC1D1 phosphorylation signatures with exercise/muscle contraction were comparable between human and mouse skeletal muscle, and AMPK regulated phosphorylation of these sites in mouse muscle, whereas contraction and exercise elicited different TBC1D4 phosphorylation patterns in mouse compared with human muscle. Our results show differential phosphorylation of TBC1D1 and TBC1D4 in response to physiological stimuli in human skeletal muscle and indicate that Akt and AMPK may be upstream kinases.